Environmental monitoring of the urban Aеolесthес sarta - Azatova Gulasal Umidbek qizi; Karabayev Azamat Xidirbayevich; Orinova Kamolaxon Otamurod qizi; Jumanoyazova Gulyora Yodgor qizi (Zien Journals, 2024)
This article presents the susceptibility and causes of Ulmus trees being damaged by Aeolesthes sarta in Khorezm region. As a result of our research, it was learned that the weaker the plants, the more susceptible they are to damage by Aeolesthes sarta
Keywords: Insect; Aeolesthes sarta; Tree; Damage; Ulmus